A pilot study into ecological burning in forests as part of a species conservation plan - Matthew W Pearson (Society for Indonesian Biodiversity, 2021)
Abstract. Pearson MW. 2021. A pilot study into ecological burning in forests as part of a species conservation plan. Biodiversitas 22: 1296-1303. Fire management and the process of managing communities has become an increasingly topical subject due to recent events. The role of fire for fuel reduction with areas set aside for conservation may not be compatible as a seed recruitment tool for Allocasuarina robusta. Presently, fire as a recruitment tool on A. robusta is not well understood. The pilot study aims to examine the latent seedbank ability to contribute to the conservation of A. robusta when ecological burning is part of a fire management plan. The investigation examined the soil seed bank beneath A. robusta before and after an ecological burn as a greenhouse experiment. The experiment results demonstrated that a diverse range of species responds to a fire that may out-compete the seed recruitment from A. robusta. The results indicate that A. robusta may not be recruiting through seed. Competition appears to be a factor that may limit the ability of A. robusta to recruit from seed.